Manejo de Spodoptera frugiperda (J. E. Smith, 1797) com uso de milho Bt e inseticidas - Burtet, Leonardo Moreira (2017)
The fall armyworm, Spodoptera frugiperda (J. E. Smith 1797) (Lepidoptera: Noctuidae), is considered the main insect-pest of corn in Brazil. Its control, in recent years, is mainly accomplished through the use of Bt plants and spray insecticides. Aiming to evaluate the efficiency of Bt proteins expressed by maize commercially available, as well as their interaction with the use of insecticides for the control of S. frugiperda to subsidize IPM and IRM programs in Bt maize, experiments were carried under field condition during two crop seasons in the 2015-16. Eight technologies of Bt maize and one non-Bt hybrid were evaluated, as well as seven insecticide application programs. Damage assessments were performed every five days, counting the number of damaged plants and assigning a score according to the Davis Scale (1992). For the application of the insecticides, a control level was established in which the spraying was carried out whenever 10% of the plants showed a damage score > 3. In the 1st season 2015/16, Agrisure TL (Cry1Ab), Herculex (Cry1F) and Optimum Intrasect (Cry1Ab/ Cry1F) and non-Bt maize required 1 to 3 sprays of insecticides to complement the control of S. frugiperda. In this season, all tested insecticides were efficient in control. In the case of YieldGard VT PRO (Cry1A.105 / Cry2Ab2), YieldGard VT PRO 3 (Cry1A.105 / Cry2Ab2 / Cry3Bb1), PowerCore (Cry1A.105 / Cry2Ab2 / Cry1F), Agrisure Viptera (Vip3Aa20) and Agrisure Viptera 3 (Vip3Aa20 / Cry1Ab) the use of insecticides was not necessary. In the second crop year 2015/16, with the exception of Agrisure Viptera and Agrisure Viptera 3, all other hybrids of Bt and non-Bt maize required 1 to 4 sprays of insecticides. The results obtained in the present work demonstrate that some Bt maize technologies (expressing genes that encode Cry1 proteins) present low control efficiency, thus making insecticides indispensable to complement the control of S. frugiperda. In contrast, the Vip3Aa20 protein shows high toxicity to S. frugiperda, showing insignificant damage to the culture. Among the insecticides tested in the work, spinetoram (12 g of a.i./ha), in general presented the highest control efficiency for fall armyworm.